Nasally delivered VEGFD mimetics mitigate stroke-induced dendrite loss and brain damage - Mauceri, Daniela; Buchthal, Bettina; Hemstedt, Thekla Joana; Weiss, Ursula; Klein, Christian D.; Bading, Hilmar (Proceedings of the National Academy of Sciences of the United States of America, 2020)
In the adult brain, vascular endothelial growth factor D (VEGFD) is required for structural integrity of dendrites and cognitive abilities. Alterations of dendritic architectures are hallmarks of many neurologic disorders, including stroke-induced damage caused by toxic extrasynaptic NMDA receptor (eNMDAR) signaling. Here we show that stimulation of eNMDARs causes a rapid shutoff of VEGFD expression, leading to a dramatic loss of dendritic structures. Using the mouse middle cerebral artery occlusion (MCAO) stroke model, we have established the therapeutic potential of recombinant mouse VEGFD delivered intraventricularly to preserve dendritic architecture, reduce stroke-induced brain damage, and facilitate functional recovery. An easy-to-use therapeutic intervention for stroke was developed that uses a new class of VEGFD-derived peptide mimetics and postinjury nose-to-brain delivery.
Gesehen am 07.05.2018